Poezja Józefa Łobodowskiego w tłumaczeniach i krytyce Światosława Hordyńskiego - Choma-Suwała, Anna (Acta Neophilologica, 2022)
This paper attempts to interpret and evaluate Ukrainian translations of Józef Łobodowski’s poetry. Already in the 1930s, he was known to the Ukrainian reader primarily as a translator of Ukrainian poetry. His original work was also particularly appreciated by the Ukrainian émigré, mainly due to its pro-Ukrainian character. One of the precursors of the translations of Łobodowski’s poetry in the Ukraine was Sviatoslav Hordynsky. In the early 1950s, he translated, inter alia, the following works: Praise of Ukraine, Horse of Ataman Łobody and October Elegy. Hordyński was also a critic of Łobodowski’s works. His critical studies: Łobodowski’s poetry and its Ukrainian motifs and Józef Łobodowski and his poetry were published in Ukrainian periodicals. These essays discuss problems concerning Polish and Ukrainian poetry from the perspective of a contemporary observer, expert, and critic of Łobodowski’s work.